Evaluation of gold (au) particle distribution in Grasberg mine material of Freeport Indonesia: fire assay approach - Akram La Kilo; Ishak Isa; Muhammad Taufiq Nur (The University of Mataram, 2023)
Freeport Indonesia is one of Freeport-McMoRan Copper & Gold Inc. affiliate companies. Freeport Indonesia conducted a series of mining and exploration processes for ore containing gold, silver, and copper. Grasberg is the mining location in PT Freeport, Indonesia. This research aimed to determine the distribution of gold (Au) particles in Grasberg rock samples with relatively high gold content. The method used for analyzing the gold content was Fire Assay. The research results indicated that the sample size affected the gold distribution in Grasberg Mine samples. An uneven distribution tendency of gold was observed in the distribution comparison of Splitter and Screen variations with normal Au content.